2019
DOI: 10.14198/medcom2019.10.2.10
|View full text |Cite
|
Sign up to set email alerts
|

Periodismo digital y empoderamiento. Tendencias informativas en noticias de Google a lo largo de 2017

Abstract: Este trabajo aborda el periodismo digital obedeciendo a dos frentes: realizar una revisión bilbliográfica sobre la actualidad del periodismo digital y su relación con el empoderamiento ciudadano, para luego realizar un estudio exploratorio sobre noticias de Google (en español) para extraer las tendencias temáticas referentes al empoderamiento y las TIC a lo largo del año 2017. La muestra de análisis se compuso de 332 noticias, divididas, principalmente, entre noticias de España y de Latinoamérica. Los resultad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
0
1
0
2
Order By: Relevance
“…UACH's observatory, which has been in charge of monitoring ethics, human rights and violence issues, has joined two observatories from other Mexican universities, such as the one in Universidad de Guadalajara (2018) that has monitored electoral issues and ITESO's, which has focused on monitoring aspects related to management, infrastructure, quality, health and risks (Paláu and Larrosa-Fuentes, 2014). Media observatories of this type are created to "obtain a responsible, ethical and professional journalism in digital media" (Valdiviezo, 2018, p. ii), as media ethics mainly centers on truth, impartiality, respect, responsibility and objectivity (Fourie, 2017), in addition to empowering citizens (García-García and Gil-Ruiz, 2019) and enabling their participation in the context of governance (Salinas, 2015). Regarding media research in Chihuahua, there are very few precedents, among them, other researchers compared nine digital news outlets (five of which are analyzed in the present study), and concluded that although news outlets have good accessibility characteristics, their quality should be improved, but it could be affected by the general insecurity that has plagued the State of Chihuahua (Salas et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…UACH's observatory, which has been in charge of monitoring ethics, human rights and violence issues, has joined two observatories from other Mexican universities, such as the one in Universidad de Guadalajara (2018) that has monitored electoral issues and ITESO's, which has focused on monitoring aspects related to management, infrastructure, quality, health and risks (Paláu and Larrosa-Fuentes, 2014). Media observatories of this type are created to "obtain a responsible, ethical and professional journalism in digital media" (Valdiviezo, 2018, p. ii), as media ethics mainly centers on truth, impartiality, respect, responsibility and objectivity (Fourie, 2017), in addition to empowering citizens (García-García and Gil-Ruiz, 2019) and enabling their participation in the context of governance (Salinas, 2015). Regarding media research in Chihuahua, there are very few precedents, among them, other researchers compared nine digital news outlets (five of which are analyzed in the present study), and concluded that although news outlets have good accessibility characteristics, their quality should be improved, but it could be affected by the general insecurity that has plagued the State of Chihuahua (Salas et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…De esta manera, García-Avilés (2017), desde la perspectiva de dependencia que menciona Catalán de la sociedad a los medios de comunicación. relaciona más al vínculo entre el periodismo online y la sociedad red, destacando que la sociedad red surge como un esquema de comunicación caracterizado por la interacción de múltiples actores entre los procesos que se desarrollan en su dinámica (García-Avilés, 2017).…”
Section: El Establecimiento De Las Características Del Periodismo Dig...unclassified
“…De esta manera, García-Avilés (2017), desde la perspectiva de dependencia que menciona Catalán de la sociedad a los medios de comunicación. relaciona más al vínculo entre el periodismo online y la sociedad red, destacando que la sociedad red surge como un esquema de comunicación caracterizado por la interacción de múltiples actores entre los procesos que se desarrollan en su dinámica (García-Avilés, 2017). Pues, en este nuevo contexto, los lazos de comunicación se generan desde cualquier punto, resultando un proceso de información que pasa por una dinámica donde las audiencias deciden sobre la información que necesitan y configurando en la manera en que quieren recibirla.…”
Section: El Establecimiento De Las Características Del Periodismo Dig...unclassified